STUDI DESKRIPTIF DETEKSI DINI PENYIMPANGAN MENTAL EMOSIONAL ( KMME, CHAT, GPPH ) PADA ANAK USIA 36 – 72 BULAN - Sri Winarsih; Nuril Nikmawati; Suprihatiningsih Suprihatiningsih (JURNAL KEBIDANAN, 2017)
Background: Health efforts since child is still in the womb until the first five years of life, aimed at maintaining the continuity of life while improving the quality of life of children in order to achieve optimal growth of physical, mental, emotional and social and has a compound intelligence according to its genetic potential (Kemenkes,2013;h.1). So as a candidate of the next generation of the nation, the quality of growth of infants in Indonesia need to get serious attention that is got good nutrition, stimulation that memadaiserta affordable by quality health services including detection and early intervention deviation grow flowers (Kemenkes, 2013, h.1). Detection and growth interventions (SDIDTK) focuses on examination of KMME, CHAT, GPPH.Objective: To describe early detection of emotional mental problems, early detection of autism, attention disorder and hyperactivity in preschoolers.Methodology: This type of research is descriptive research. The author only describes the implementation of early detection of mental emotional deviation of children aged 36-72 months.Results: the majority of KMME studies of 40 respondents were in an abnormal category 26 (65%) and at CHAT of 40 respondents in abnormal category there were 5 (12.5%), in GPPH from 40 respondents there were 2 children falling into the category abnormal.Conclusion: The conclusion is that early detection of developmental disorder in KMME, CHAT, GPPH, the village midwife meetings with parents to conduct counseling and provide stimulation and intervention. After three months of evaluation, there is no change in referral to the hospital.